Examining the Role of Educational Background and Organizational Work Culture in Enhancing School Laboratory Management Performance: A Quantitative Study in Indonesian Junior High Schools - Ade Fira Pratiwi Mokodompit; Harol R. Lumapow; Romi J. Mongdong (International Journal of Information Technology and Education, 2026)
This study investigates the influence of laboratory head educational background and organizational work culture on laboratory management performance in junior secondary schools. Effective laboratory management plays a critical role in supporting science-based learning; however, many schools face challenges related to inadequate human resource competencies and weak organizational culture. This research employs a quantitative explanatory approach to examine both the individual and simultaneous effects of these variables. The population consisted of laboratory heads from 30 junior secondary schools in East Bolaang Mongondow Regency, Indonesia, using a total sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings reveal that the educational background of laboratory heads has a significant positive effect on laboratory management performance, particularly in areas of technical competence, planning, and administrative management. Additionally, work culture—characterized by discipline, collaboration, responsibility, and professional commitment—also shows a significant positive influence on management effectiveness. Simultaneously, both variables contribute substantially to improving laboratory performance, indicating that the integration of individual competence and organizational culture is essential for optimal management. The study highlights that schools with well-qualified laboratory heads and strong work culture tend to demonstrate more systematic laboratory administration, better equipment maintenance, and more effective implementation of practical activities. This research contributes to the literature on educational management by providing empirical evidence on the combined effects of human capital and organizational culture in school laboratory settings. The findings offer practical implications for policymakers and school leaders to strengthen professional qualifications and foster a positive work culture to enhance the quality of science education.